2017
DOI: 10.1017/s0022029916000777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parity, milking time and stage of lactation on milk yield of Jiangyue donkey (Equus asinus) in North West China

Abstract: The study reported in this Research Communication was carried out to examine how parity and milking time affected donkey milk yield under a typical Chinese production system. Eighteen Jiangyue breed donkeys with good health condition, aged between 6 and 9 years, and with parities 3 and 4, were selected. Milk production was measured commencing from the fourth week post-foaling, with a total data collection of 170 d in milk (lactation length). Mean milk yield of the donkeys used in this study was 3·0 kg/donkey/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The average milk yield collected is reported in Table 1 (1100 h: 585.71 ± 220.78 mL; 1700 h: 728.15 ± 171.71 mL) was in the range found for other donkey farms in Italy, for which the average individual milk yield varied between 1 and 2 L per day (Dai et al, 2017); it was also in line with previous works on the same breed (Salari et al, 2020). However, the literature varies considerably with respect to the average milk yield per milking among donkey breeds, from 172 mL for the Littoral Dinaric breed to 1,000 mL for the Jiangyue breed (Ivanković et al, 2009;Muhatai et al, 2017). These differences could be due to the absence of genetic selection for the production of milk in this species.…”
Section: Resultssupporting
confidence: 88%
“…The average milk yield collected is reported in Table 1 (1100 h: 585.71 ± 220.78 mL; 1700 h: 728.15 ± 171.71 mL) was in the range found for other donkey farms in Italy, for which the average individual milk yield varied between 1 and 2 L per day (Dai et al, 2017); it was also in line with previous works on the same breed (Salari et al, 2020). However, the literature varies considerably with respect to the average milk yield per milking among donkey breeds, from 172 mL for the Littoral Dinaric breed to 1,000 mL for the Jiangyue breed (Ivanković et al, 2009;Muhatai et al, 2017). These differences could be due to the absence of genetic selection for the production of milk in this species.…”
Section: Resultssupporting
confidence: 88%
“…In terms of the quantitative milk production, previous studies on a few mainly European and Chinese donkey breeds, have highlighted a high variability (D'alessandro and Martemucci 2012;Martini et al 2014a;Muhatai et al 2017). Several of these authors have also found that a higher milk yield occurs in the first 3 months of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of parity on the quantity and quality of milk has been widely demonstrated in cows, especially primiparous cows which tend to produce less milk. However, little is known about donkeys used for milk production [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%